Interactive Multimedia Based on Local Wisdom “Ngusaba Tipat” to Improves Science Learning Outcomes of Grade IV Elementary School Students - Ayuni, Ni Kadek Risq; Kristiantari, Maria Goreti Rini; Paramita, Made Vina Arie (Universitas Pendidikan Ganesha, 2025)
Low student learning outcomes in the Science and Social Studies (IPAS) subject remain a challenge in elementary education. One contributing factor is the lack of innovative learning media to support students' engagement and improve learning achievements effectively. This study aims to analyze the instructional design, assess the feasibility, and evaluate the effectiveness of interactive multimedia based on local wisdom “Ngusaba Tipat” in improving elementary school students’ IPAS learning outcomes. The research employed a development research design using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study involved subject matter experts, instructional design experts, media experts, teachers, a principal, and 28 fourth-grade students. Data were collected through observations, interviews, questionnaires, and learning outcome tests. Data analysis techniques included descriptive qualitative, descriptive quantitative, and independent sample t-test. The results indicated that the developed interactive multimedia achieved a very good feasibility score in all expert reviews and practicality tests. Furthermore, the effectiveness test showed that the tvalue = 3.332 was higher than the ttable = 1.711 at a 5% significance level, indicating that the multimedia was effective in improving students’ learning outcomes. These findings suggest that integrating local wisdom into digital learning media can serve as an alternative culturally-based learning strategy in elementary education.